Metallic monoboronyl compounds: Prediction of their structure and comparison with the cyanide analogues. Issue 11 (12th February 2017) - Vega‐Vega, Álvaro; Barrientos, Carmen; Largo, Antonio
Abstract : A theoretical study of monoboronyls of different metals has been carried out. We have chosen Mg as representative of s‐block elements, Al for the p‐block, and Group 11 metals (Cu, Ag, and Au) for the d‐block. Different behaviors are observed: bonding through the oxygen atom is preferred in the case of Al, for all Group 11 monoboronyls bonding through the boron atom prevails and both interactions give rise to almost isoenergetic compounds in the case of Mg. Predictions for the spectroscopic parameters relevant for rotational and vibrational spectroscopy of the different competitive species are provided. Al and Group 11 boronyls have relatively high dissociation energies, whereas Mg boronyl has moderate dissociation energy. The molecular structure of metal boronyls has been rationalized through an analysis of the bonding. The similarities and differences between metal boronyls and their isoelectronic cyanide analogues have been discussed. © 2017 Wiley Periodicals, Inc. Abstract : Monoboronyls of representative metals are theoretically studied. Mg (s‐block), Al (p‐block), and Group 11 metals Cu, Ag, and Au (d‐block) have been chosen. The preference for metal‐boron or metal‐oxygen bonding is discussed and relevant spectroscopic parameters predicted. A comparison with the analogue metal‐cyanide compounds is carried out emphasizing the similarities and differences between the isoelectronic boronyl and cyanide ligands.